Assessment of Observational Evidence for Direct Convective Hydration of the Lower Stratosphere. Issue 15 (29th July 2020) - Jensen, E. J.; Pan, Laura L.; Honomichl, Shawn; Diskin, Glenn S.; Krämer, Martina; Spelten, Nicole; Günther, Gebhard; Hurst, Dale F.; Fujiwara, Masatomo; Vömel, Holger; Selkirk, Henry B.; Suzuki, Junko; et al.
Abstract: In situ and remote sensing observations of water vapor are analyzed to assess the evidence for direct convective hydration of the lower stratosphere. We have examined several hundred balloon‐borne and airborne in situ measurements of lower stratospheric humidity in the tropics and northern midlatitudes. We find that the tropical lower stratospheric H2 O enhancements above the background occur quite infrequently, and the height of the enhancements is within about 1 km of the cold‐point tropopause. Following Schwartz et al. (2013, https://doi.org/10.1002/grl.50421 ), we examine the anomalously high (above 8 ppmv) water vapor mixing ratios retrieved by the Aura Microwave Limb Sounder (MLS) at 100‐ and 82‐hPa pressure levels, and we determine their vertical location relative to the local tropopause based on both Global Forecast System (GFS) operational analysis and the ERA5 reanalysis temperature data. We find that essentially all of the >8‐ppmv MLS water vapor measurements over the extratropical North American monsoon region are above the relatively low lapse‐rate tropopause in the region, and most are above the local cold‐point tropopause. Over the Asian monsoon region, most (80/90%) of the high H2 O values occur below the relatively high‐altitude local lapse‐rate/cold‐point tropopause. Anomalously high MLS water vapor retrievals at 100 and 82 hPa almost never occur in the deep tropics. We show that this result is consistent with the in situ observations given the broad vertical averaging kernel of the MLS measurement. The available evidence suggests that direct hydration of the lower stratosphere is important over North America during the monsoon season but likely has limited impact in the tropics. Key Points: Evidence for direct convective hydration of the lower stratosphere is assessed with in situ and remote sensing measurements Direct convective hydration of the extratropical lower stratosphere occurs primarily over North America during summertime Direct convective hydration of the tropical lower stratosphere is rare and limited to slight enhancements just above the tropopause